Ископаемые черепахи семейства Sinochelyidae - Чхиквадзе, В.М. (Вестник зоологии, 1985)
A revision of Lower Cretacean turtles of China and Mongolia, assigned to genera Sinochelys, Scutemys and Peishanemys, bear an evidence of synonymy of Sinochelys applanata Wim a n, 1930 and Scutemys tecta Wiman, 1930, representatives of two monotypic genera. Nessovemys gen. n. is established to include Peishanemys testudiformis Nessov, 1981-it occupies an intermediate position between Sinochelys and Peishanemys, being somewhat closer to the former. Turtles of the family Sinochelyidae are suggested to be the most probable ancestors of terrestrial Testudinidae.